2019
DOI: 10.1503/cmaj.181067
|View full text |Cite
|
Sign up to set email alerts
|

Risk of severe maternal morbidity associated with cesarean delivery and the role of maternal age: a population-based propensity score analysis

Abstract: esarean delivery is a useful intervention for mothers and newborns in many situations. Nonetheless, its rates have soared over the past 20 years in most developed countries, where more than 1 out of 5 women deliver by cesarean. 1 The range of indications for cesarean delivery appears to have broadened considerably, with more cesarean deliveries likely to be performed for questionable medical indications. 2-7 This increase requires evaluation of its potential adverse consequences on maternal and neonatal health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 35 publications
3
54
0
3
Order By: Relevance
“…The definitions of infection and postpartum hemorrhage used in previous studies, which did not focus on severe cases, may explain this difference. The increased risk of severe postpartum hemorrhage observed in our study is consistent with results in singleton pregnancies [17][18][19] . The higher risk in singletons is especially marked for cesareans during labor and for cesareans during the second stage of labor 19,20 -both conditions met by cesareans for second twins.…”
Section: Discussionsupporting
confidence: 92%
“…The definitions of infection and postpartum hemorrhage used in previous studies, which did not focus on severe cases, may explain this difference. The increased risk of severe postpartum hemorrhage observed in our study is consistent with results in singleton pregnancies [17][18][19] . The higher risk in singletons is especially marked for cesareans during labor and for cesareans during the second stage of labor 19,20 -both conditions met by cesareans for second twins.…”
Section: Discussionsupporting
confidence: 92%
“…Although postpartum pain is common among women who deliver babies either by vaginal or ceasarian modes, it has been reported in many studies that postpartum pain is rampantly observed within an extended period of time among women who have undergone ceasarian birth delivery [1,2]. CS delivery had also been associated with higher risk of severe acute maternal morbidity (SAMM) than vaginal delivery particularly in women who are 35 years or older [3]. Studies recommend the control of the CS through the use of Robson classification or policy instruments at the health system level [4].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, two management options are available: planned cesarean and planned vaginal delivery. [2][3][4] There fore, the only clinically relevant finding in this study 1 is that there was no signifi cant increase in the risk of SAMM after planned cesarean delivery (adjusted odds ratio 1.09, 95% confidence interval 0.85-1.41).…”
mentioning
confidence: 51%
“…3,4 Neither the Term Breech Trial (n = 2088) 3 nor the Twin Births Study (n = 2804) 4 showed any association between planned cesarean delivery and SAMM. Although these trials were limited in size (given the low frequency of SAMM), their findings (and those of less valid, nonexperimental studies) 1,6 are consistent with a nearzero rate difference in SAMM between planned cesarean and planned vaginal delivery.…”
mentioning
confidence: 79%